Detection of propadiene (CH2CCH2), propene (C3H6) and non-detection of propane (C3H8) in Jupiter’s northern polar stratosphere - James A. Sinclair; Thomas K. Greathouse; Rohini S. Giles; Keeyoon Sung; Conor A. Nixon; Nicholas A. Lombardo; Vincent Hue; Julianne I. Moses; Leigh N. Fletcher; Patrick G.J. Irwin; Glenn S. Orton (Icarus, 2026)

How much Copper Do Calves Need? Retention and Hepatic Storage in Artificially Reared Milk-Fed Holstein–Friesian Calves - Amy P. Marsh; Liam A. Sinclair; Joe M. Roberts; Alexander M. Mackenzie; Stefan E. Yerby; James A. Huntington; James H. McCaughern (Biological Trace Element Research, 2026)
Excessive copper (Cu) absorption in calves may increase the risk of excessive hepatic Cu accumulation, likely driven by their elevated pre-ruminant absorptive capacity, with the potential for harmful Cu accumulation leading to adverse health and productivity outcomes. However, quantitative data across the weaning transition remains limited. This study utilized secondary data and bio-banked samples from 35 Holstein–Friesian bull calves to estimate hepatic Cu retention coefficients pre- and post-weaning. Although mean hepatic Cu concentrations remained broadly stable throughout the study, between 311 and 675 mg/kg of DM, changes varied by developmental stage: calves experienced hepatic Cu accumulation of 2.5 mg of Cu/kg of DM/d pre-weaning but a net reduction of 1.8 mg/kg of DM/d post-weaning. Pre-weaning calves exhibited a hepatic Cu retention coefficient of 81% compared to post-weaning calves, where the hepatic Cu retention coefficient was 5%. This reduction in absorptive capacity is consistent with increased rumen development and greater antagonism from dietary sulfur and molybdenum. Hepatic steady-state Cu intake requirements were estimated at 3 mg/kg of DM pre-weaning and 15 mg/kg of DM post-weaning. These findings demonstrate that the pre-weaning period represents a phase of high Cu retention and heightened susceptibility to hepatic Cu accumulation, even when dietary Cu meets current recommendations. Refining Cu feeding guidelines to more accurately reflect developmental stage and rumen maturation may help prevent excessive hepatic Cu loading while maintaining adequate mineral supply.

Recovering European River Invertebrate Communities Homogenize or Differentiate Depending on Anthropogenic Stress - Daniela Cortés‐Guzmán; Diana E. Bowler; Marie Anne Eurie Forio; Peter Goethals; Ioannis Karaouzas; Ariane Moulinec; James S. Sinclair; Rudy Vannevel; Peter Haase; Ellen A. R. Welti (Global Change Biology, 2026)
Biodiversity loss can lead to biotic homogenization, whereby local communities within a region become increasingly similar over time, resulting in simplified communities with reduced functionality. However, our understanding of whether alleviating anthropogenic stress can reverse homogenization and promote biotic differentiation (i.e., increasing dissimilarity) remains limited, partly because the effectiveness of conservation actions is often assessed only at the local scale (e.g., increases in local diversity). Here, we examined evidence for biotic differentiation in European river invertebrate communities, a system that has generally shown signs of local recovery. We analyzed 447 time series of river invertebrate communities from 1994 to 2023, spanning 48 river basins across 15 European countries. We then related trends in community similarity within each basin, measured as taxonomic and trait β‐diversity, to spatial gradients of anthropogenic stress, including ecological quality (a proxy of general anthropogenic stress), air temperature increase, and land cover pressure. β‐diversity trends were strongly mediated by anthropogenic stress levels, with communities in lower‐stress basins showing differentiation, while those in higher‐stress basins homogenized. In addition, we found that the direction of β‐diversity change depended less on taxa or traits being gained or lost, and more on the identity of the traits involved, highlighting how trait composition mediates community responses to anthropogenic change. Specifically, additions promoted differentiation at lower stress levels but contributed to homogenization under conditions of higher stress, whereas subtractions exhibited the inverse pattern. Our results demonstrate that β‐diversity responds asymmetrically to spatial variation in anthropogenic stress, with both homogenization and differentiation occurring within a system that is, overall, undergoing recovery. Recognizing the stress‐dependent responses of β‐diversity allows researchers and managers to more accurately assess conservation success and provide recommendations that promote long‐term ecosystem structural and functional recovery.

Effects of land cover and protected areas on flying insect diversity - James S. Sinclair; Dominik Buchner; Mark O. Gessner; Jörg Müller; Steffen U. Pauls; Stefan Stoll; Ellen A. R. Welti; Claus Bässler; Jörn Buse; Frank Dziock; Julian Enss; Thomas Hörren; et al. (Conservation Biology, 2025)
Widespread insect losses are a critical global problem. Mitigating this problem requires identifying the principal drivers across different taxa and determining which insects are covered by protected areas. However, doing so is hindered by missing information on most species owing to extremely high insect diversity and difficulties in morphological identification. To address this knowledge gap, we used one of the most comprehensive insect DNA metabarcoding data sets assembled (encompassing 31,846 flying insect species) in which data were collected from a network of 75 Malaise traps distributed across Germany. Collection sites encompass gradients of land cover, weather, and climate, along with differences in site protection status, which allowed us to gain broader insights into how insects respond to these factors. We examined changes in total insect biomass, species richness, temporal turnover, and shifts in the composition of taxa, key functional groups (pollinators, threatened species, and invasive species), and feeding traits. Lower insect biomass generally equated to lower richness of all insects and higher temporal turnover, suggesting that biomass loss translates to biodiversity loss and less stable communities. Spatial variability in insect biomass and composition was primarily driven by land cover, rather than weather or climate change. As vegetation and land‐cover heterogeneity increased, insect biomass increased by 50% in 2019 and 56% in 2020 and total species richness by 58% and 33%, respectively. Similarly, areas with low‐vegetation habitats exhibited the highest richness of key taxa, including pollinators and threatened species, and the widest variety of feeding traits. However, these habitats tended to be less protected despite their higher diversity. Our results highlight the value of heterogeneous low vegetation for promoting overall insect biomass and diversity and that better protection of insects requires improved protection and management of unforested areas, where many biodiversity hotspots and key taxa occur.

A Re-evaluation of the Optimal Liver Copper Concentrations for Health, Performance and Fertility of Replacement Holstein–Friesian Heifers - Amy P. Marsh; Liam A. Sinclair; Joe M. Roberts; Alexander M. Mackenzie; James H. McCaughern (Biological Trace Element Research, 2025)

Fish as environmental sentinels for metal contaminants of human health concern in the Lower Mississippi River Basin - Scoty Hearst; Trent Selby; Joseph Kazery; Steven Everman; Manliang Feng; Lillian Sisson; Chinaza Nwaiwu; Alison Cevallos; James Lock; Matthew Sinclair (Journal of Trace Elements in Medicine and Biology, 2025)

Recovery and Degradation Drive Changes in the Dispersal Capacity of Stream Macroinvertebrate Communities - Carlos Cano‐Barbacil; James S. Sinclair; Ellen A. R. Welti; Peter Haase (Global Change Biology, 2025)
Freshwater ecosystems face significant threats, including pollution, habitat loss, invasive species, and climate change. To address these challenges, management strategies and restoration efforts have been broadly implemented. Across Europe, such efforts have resulted in overall improvements in freshwater biodiversity, but recovery has stalled or failed to occur in many localities, which may be partly caused by the limited dispersal capacity of many species. Here, we used a comprehensive dataset comprising 1327 time series of freshwater macroinvertebrate communities ranging from 1968 to 2021 across 23 European countries to investigate whether dispersal capacity changes with the ecological quality of riverine systems. Sites experiencing improvements in ecological quality exhibited a net gain in species and tended to have macroinvertebrate communities containing species with stronger dispersal capacity (e.g., active aquatic and aerial dispersers, species with frequent propensity to drift, and insects with larger wings). In contrast, sites experiencing degradation of ecological quality exhibited a net loss of species and a reduction in the proportion of strong dispersers. However, this response varied extensively among countries and local sites, with some improving sites exhibiting no parallel gains in macroinvertebrates with higher dispersal capacity. Dispersal capacity of the local species pool can affect the success of freshwater ecosystem restoration projects. Management strategies should focus on enhancing landscape connectivity to create accessible “source” areas and refugia for sensitive taxa, especially as climate change reshapes habitat suitability. Additionally, biodiversity initiatives must incorporate adaptive decision‐making approaches that account for the site‐specific responses of macroinvertebrate communities to changes in ecological quality.

Ecological but Not Biological Traits of European Riverine Invertebrates Respond Consistently to Anthropogenic Impacts - James S. Sinclair; Rachel Stubbington; Ralf B. Schäfer; Libuše Barešová; Núria Bonada; Zoltán Csabai; J. Iwan Jones; Aitor Larrañaga; John F. Murphy; Petr Pařil; Marek Polášek; Jes J. Rasmussen; et al. (Global Ecology and Biogeography, 2024)
Aim To determine which riverine invertebrate traits respond consistently to anthropogenic impacts across multiple biogeographic regions. Location Europe. Time Period 1981–2021. Major Taxa Studied Riverine invertebrates. Methods We compiled a database of riverine invertebrate community time series for 673 sites across six European countries spanning six freshwater ecoregions. We compared trait responses to anthropogenic impacts (quantified as changes in ‘ecological quality’) among regions for seven ‘ecological’ traits, which reflect habitat preferences, and nine ‘biological’ traits (e.g., morphology or life history), which represent taxon‐specific attributes that can influence ecosystem processes. Results Four ecological traits (current, microhabitat, salinity and trophic preferences) and one biological trait (dispersal mode) responded consistently across regions. These responses were primarily driven by spatial differences among poorer to better quality sites. Responses to temporal changes in quality were comparable but less pronounced. Main Conclusions Consistent responses to anthropogenic impacts across multiple ecological traits indicate these traits may improve broader scale measurements, comparisons and predictions of community responses. However, we could not use ecological traits to identify the actions of specific stressors because multiple traits always responded as a group. Inconsistent responses across almost all biological traits indicated that these traits may be less predictive of impacts across regions. Predictions of how biological traits, and associated ecosystem processes, respond to anthropogenic impacts may be most effective at regional scales where responses are more consistent.

Dispersal, glacial refugia and temperature shape biogeographical patterns in European freshwater biodiversity - Daniela Cortés‐Guzmán; James Sinclair; Christian Hof; Jan B. Kalusche; Peter Haase (Global Ecology and Biogeography, 2024)
Aim Temperature is regarded as an important driver of broad‐scale biodiversity patterns. However, less is known of the role of dispersal in shaping broad‐scale species and trait distributions, particularly given that species had to disperse out of glacial refugia after the Last Glacial Maximum (LGM). Here, we used a unique dataset describing the distributions of freshwater fauna combined with trait information to evaluate biodiversity relationships to distance to glacial refugia and temperature. Location Twenty‐five biogeographical regions across Europe. Time Period Data from species occurrence were gathered in 1978. Major Taxa Studied A total of 2816 freshwater invertebrate species and 230 freshwater fish species. Methods Using the occurrence of invertebrate and fish species in the biogeographical regions, and publicly available trait information, we analysed patterns in diversity indices (i.e. species richness, trait richness and trait redundancy), trait distribution and species and trait β ‐diversity, and their relationship to distance to known glacial refugia and regional temperature. Results We show that distributions of European invertebrate and fish species and traits are primarily explained by distance to refugia and its covarying effect with temperature (i.e. refugia tend to be warmer). Specifically, species and trait richness were higher in regions proximate to refugia and lower in distant regions. Additionally, communities in colder and distant regions exhibited reduced niche dimensions and slower life histories, suggesting increased vulnerability to environmental change. Main Conclusions Species more distant from their refugia were characterized by higher dispersal capacities. Accordingly, since the LGM, only a subset of species was able to colonize distant regions, while many species have spatial ranges constrained by their dispersal capacity, increasing their potential for extinction under ongoing climate change. Therefore, additional conservation measures considering species' dispersal capacities are required.

Saturn’s seasonal variability from four decades of ground-based mid-infrared observations - James S.D. Blake; L.N. Fletcher; G.S. Orton; A. Antuñano; M.T. Roman; Y. Kasaba; T. Fujiyoshi; H. Melin; D. Bardet; J.A. Sinclair; M. Es-Sayeh (Icarus, 2023)

Saturn’s atmospheric response to the large influx of ring material inferred from Cassini INMS measurements - Julianne I. Moses; Zarah L. Brown; Tommi T. Koskinen; Leigh N. Fletcher; Joseph Serigano; Sandrine Guerlet; Luke Moore; J. Hunter Waite; Lotfi Ben-Jaffel; Marina Galand; Joshua M. Chadney; Sarah M. Hörst; et al. (Icarus, 2023)

Are stormwater detention ponds protecting urban aquatic ecosystems? a case study using depressional wetlands - Kayla M. Hess; James S. Sinclair; Alexander J. Reisinger; Eban Z. Bean; Basil V Iannone III (Urban Ecosystems, 2022)

Functional traits reveal the dominant drivers of long‐term community change across a North American Great Lake - James S. Sinclair; Michael E. Fraker; James M. Hood; Kenneth T. Frank; Mark R. DuFour; Ann Marie Gorman; Stuart A. Ludsin (Global Change Biology, 2021)
Ecosystems worldwide have been impacted by multiple anthropogenic stressors, yet efforts to understand and manage these impacts have been hindered by difficulties in disentangling relative stressor effects. Theoretically, the actions of individual stressors can be delineated based on associated changes in functional traits and these relationships should be generalizable across communities comprised of different species. Thus, combining trait perspectives with community composition data could help to identify the relative influence of different stressors. We evaluated the utility of this combined approach by quantifying shifts in fish species and trait composition in Lake Erie during the past 50 years (1969–2018) in relation to human‐driven changes in nutrient inputs, climate warming, and biological invasions. Species and trait shifts were also compared between two Lake Erie basins, which differ in their environmental and biological characteristics, to identify trait responses that were generalizable across different ecosystems versus those that were context dependent. Our analyses revealed consistent species changes across basins, and shifts in feeding and thermal traits, that were primarily associated with altered nutrient inputs (oligotrophication followed by eutrophication). We found no or inconsistent trait‐based evidence for the effects of warming and two invasive fishes. Context‐dependent trait responses were also evident; nutrient inputs were related to shifts in species tolerant of turbidity in the shallow, eutrophic western basin, which contrasted to shifts between benthopelagic and benthic species in the deeper central basin. Our results reveal the dominant effects of specific stressors on a large freshwater lake and offer a framework for combining species‐based and trait‐based approaches to delineate the impacts of simultaneous stressors on communities of perturbed natural ecosystems.

Vegetation management and benthic macroinvertebrate communities in urban stormwater ponds: implications for regional biodiversity - James S. Sinclair; Lindsey S. Reisinger; Carrie R. Adams; Eban Bean; Alexander J. Reisinger; Basil V. Iannone (Urban Ecosystems, 2021)

Consistent and transient drivers of freshwater zooplankton communities - James S. Sinclair; Shelley E. Arnott; William A. Nelson; Kaitlyn B. Brougham (Journal of Biogeography, 2021)
Aim Inferences of the predominant processes that structure communities are commonly based on single ‘snapshots’ in time, which may miss temporally transient but important mechanisms. In this study, we compared key environmental and spatial drivers of zooplankton composition across multiple years to quantify shifts in their relative importance through time, and to identify any drivers of temporal change. Location Southern Ontario, Canada. Taxon Zooplankton. Methods Zooplankton were collected from 29 lakes in southern Ontario, Canada over four years (2013–2016). Variation partitioning was used to quantify the relative importance of independent and covarying components of local environmental conditions, regional east‐west and north‐south compositional trends, and inter‐lake geographic distance in each year. Measured environmental metrics included aspects of lake morphology and chemistry, and spatial relationships were quantified using lake latitude/longitude coordinates and Moran's Eigenvector Maps (MEMs). Redundancy analyses (RDAs) were also used to compare the influence of individual environmental and spatial variables across years. Results Most local‐scale and regional‐scale community processes were consistently important across all surveyed years, but some were less consistent. Specifically, geomorphology was always an important driver of local environmental and regional spatial community patterns. This occurred because local community composition was strongly affected by whether a lake was shallower versus deeper, and due to spatial clusters of shallow and deep lakes that produced negative spatial autocorrelation in community composition. Conversely, the individual influences of lake chemistry and spatial east‐west compositional trends were important in some years and not in others, potentially due to inter‐annual shifts in the predominant environmental variables and extreme weather events. Main conclusions A single‐year community snapshot can provide insight into consistent or slowly changing community structuring processes, such as those driven by geomorphology, but may not completely capture temporally transient mechanisms. Furthermore, snapshots collected during anomalous seasons or years may misrepresent which mechanisms are predominantly determining community composition. Future efforts to understand local and regional community drivers would therefore benefit from considering which processes are likely temporally ‘consistent’ versus ‘transient’, and studies with more variable components would benefit from considering or controlling for temporal shifts in their importance.

A framework for predicting which non-native individuals and species will enter, survive, and exit human-mediated transport - James S. Sinclair; Julie L. Lockwood; Sarah Hasnain; Phillip Cassey; Shelley E. Arnott (Biological Invasions, 2020)

A Systematic Review of How Multiple Stressors From an Extreme Event Drove Ecosystem-Wide Loss of Resilience in an Iconic Seagrass Community - Gary A. Kendrick; Robert J. Nowicki; Ylva S. Olsen; Simone Strydom; Matthew W. Fraser; Elizabeth A. Sinclair; John Statton; Renae K. Hovey; Jordan A. Thomson; Derek A. Burkholder; Kathryn M. McMahon; Kieryn Kilminster; et al. (Frontiers in Marine Science, 2019)

The effectiveness of bench press training with or without throws on strength and shot put distance of competitive university athletes - Akihiro Sakamoto; Akihiro Kuroda; Peter James Sinclair; Hisashi Naito; Kazuhiko Sakuma (European Journal of Applied Physiology, 2018)

Cranial morphological scaling and relative prey size limitations for a native predator in an invaded system - Eliza I. Gilbert; Scott L. Durst; Angela P. James; Jason E. Davis; Thomas B. Sinclair; Nathan R. Franssen (Environmental Biology of Fishes, 2018)

International Trials of Vertical Flow Reactors for Coal Mine Water Treatment - Ivan Blanco; Devin J. Sapsford; Dave Trumm; James Pope; Natalie Kruse; Young-wook Cheong; Hamish McLauchlan; Eden Sinclair; Paul Weber; William Olds (Mine Water and the Environment, 2018)

Water–fat MRI in a hibernator reveals seasonal growth of white and brown adipose tissue without cold exposure - Amanda MacCannell; Kevin Sinclair; Lannette Friesen-Waldner; Charles A. McKenzie; James F. Staples (Journal of Comparative Physiology B, 2017)

Relative importance of colonist quantity, quality, and arrival frequency to the extinction of two zooplankton species - James S. Sinclair; Shelley E. Arnott (Oecologia, 2017)

Mutations in KIAA0753 cause Joubert syndrome associated with growth hormone deficiency - Joshi Stephen; Thierry Vilboux; Luhe Mian; Chulaluck Kuptanon; Courtney M. Sinclair; Deniz Yildirimli; Dawn M. Maynard; Joy Bryant; Roxanne Fischer; Meghana Vemulapalli; James C. Mullikin; Marjan Huizing; et al. (Human Genetics, 2017)

Strength in size not numbers: propagule size more important than number in sexually reproducing populations - James S. Sinclair; Shelley E. Arnott (Biological Invasions, 2016)

Rapid conversion of EUCOMM/KOMP-CSD alleles in mouse embryos using a cell-permeable Cre recombinase - Edward Ryder; Brendan Doe; Diane Gleeson; Richard Houghton; Priya Dalvi; Evelyn Grau; Bishoy Habib; Evelina Miklejewska; Stuart Newman; Debarati Sethi; Caroline Sinclair; Sapna Vyas; et al. (Transgenic Research, 2014)

Reply to “Attempting to better define intensity for muscular performance; is it all wasted effort?” - Akihiro Sakamoto; Peter James Sinclair (European Journal of Applied Physiology, 2012)

Muscle activations under varying lifting speeds and intensities during bench press - Akihiro Sakamoto; Peter James Sinclair (European Journal of Applied Physiology, 2012)

Baseline Ecological Risk Assessment of the Calcasieu Estuary, Louisiana: Part 3. An Evaluation of the Risks to Benthic Invertebrates Associated With Exposure to Contaminated Sediments - Donald D. MacDonald; Christopher G. Ingersoll; Nile E. Kemble; Dawn E. Smorong; Jesse A. Sinclair; Rebekka Lindskoog; Gary Gaston; Denise Sanger; R. Scott Carr; James Biedenbach; Ron Gouguet; John Kern; et al. (Archives of Environmental Contamination and Toxicology, 2011)

Discovery of Acropora palmata at the Flower Garden Banks National Marine Sanctuary, northwestern Gulf of Mexico - Beth Zimmer; William Precht; Emma Hickerson; James Sinclair (Coral Reefs, 2006)

RETROSPECTIVE ISOTOPIC ANALYSES OF STELLER SEA LION TOOTH ANNULI AND SEABIRD FEATHERS: A CROSS‐TAXA APPROACH TO INVESTIGATING REGIME AND DIETARY SHIFTS IN THE GULF OF ALASKA - Keith A. Hobson; Elizabeth H. Sinclair; Anne E. York; James R. Thomason; Richard E. Merrick (Marine Mammal Science, 2004)
A bstract Stable isotope (δ 15 N and δ 13 C) values of individual tooth annuli of female Steller sea lions ( n = 120) collected from the 1960s through the 1980s were used for retrospective analyses of temporal changes in food webs in the Gulf of Alaska and North Pacific Ocean. We also examined isotopically contour feathers of tufted puffins ( n = 135) and crested auklets ( n = 37) through this period to test for broader isotopic patterns indicative of whole food web changes. Steller sea lions decreased slightly in δ 13 C and increased in δ 15 N values, suggesting an increasing trophic level and change in foraging location or oceanographic isotopic signature. Steller sea lion first and second tooth annuli were enriched in 15 N and depleted in 13 C compared with subsequent annuli, indicating the effects of maternal influence through weaning. The general pattern of increasing δ 15 N values among Steller sea lions supports previous conclusions regarding a reduction or redistribution of forage fishes and an increase of demersal and semi‐demersal species in the North Pacific ecosystem. There were no significant changes in δ 15 N values for either bird species. However, δ 13 C values in both bird species again suggested changes in foraging location or a shift in oceanographic currents.